From Historical Models to Virtual Heritage Simulations - Champion, Erik (arthistoricum.net, 2019)
This chapter analyses the gap between digital historical models, and proposes that instead of developing stand-alone models that we design in terms of components, components of scholarly ecosystems and audienceoriented learning systems. The focus here is not on individual projects or technological limitations but on the lack of clear and replicable explicit terminology, methodology, assessable, replicable evaluation, and scholarly infrastructure. The success of virtual heritage projects as both a communication and preservation medium depend on community involvement, including scholars, students, the wider public, but also the original shareholders. There is also great potential for more focussed usability studies to verify the effectiveness of interaction and contextual learning. How interaction is intended, what actually takes place and how to archive it separately from the model are difficult issues, but they need to be solved. I will also briefly discuss four major themes potentially of great import to a virtual heritage repository: consumer VR; research groups attempting to avoid the problems of silo projects; publication of 3D models in journals; and real-time streaming of distributed components in a game engine. This chapter also suggests ten criteria to determine whether and to what extent virtual heritage models can solves these issues.